Framework for Equitable Allocation of COVID-19 Vaccine - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
In response to the coronavirus disease 2019 (COVID-19) pandemic and the societal disruption it has brought, national governments and the international community have invested billions of dollars and immense amounts of human resources to develop a safe and effective vaccine in an unprecedented time frame. Vaccination against this novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), offers the possibility of significantly reducing severe morbidity and mortality and transmission when deployed alongside other public health strategies and improved therapies. Health equity is intertwined with the impact of COVID-19 and there are certain populations that are at increased risk of severe illness or death from COVID-19. In the United States and worldwide, the pandemic is having a disproportionate impact on people who are already disadvantaged by virtue of their race and ethnicity, age, health status, residence, occupation, socioeconomic condition, or other contributing factors. Framework for Equitable Allocation of COVID-19 Vaccine offers an overarching framework for vaccine allocation to assist policy makers in the domestic and global health communities. Built on widely accepted foundational principles and recognizing the distinctive characteristics of COVID-19, this report's recommendations address the commitments needed to implement equitable allocation policies for COVID-19 vaccine.
Keywords: Health and Medicine

Ranking Vaccines: A Prioritization Framework: Phase I: Demonstration of Concept and a Software Blueprint - Institute of Medicine (The National Academies Press, 2012)
As a number of diseases emerge or reemerge thus stimulating new vaccine development opportunities to help prevent those diseases, it can be especially difficult for decision makers to know where to invest their limited resources. Therefore, it is increasingly important for decision makers to have the tools that can assist and inform their vaccine prioritization efforts. In this first phase report, the IOM offers a framework and proof of concept to account for various factors influencing vaccine prioritization-demographic, economic, health, scientific, business, programmatic, social, policy factors and public concerns. Ranking Vaccines: A Prioritization Framework describes a decision-support model and the blueprint of a software-called Strategic Multi-Attribute Ranking Tool for Vaccines or SMART Vaccines. SMART Vaccines should be of help to decision makers. SMART Vaccines Beta is not available for public use, but SMART Vaccines 1.0 is expected to be released at the end of the second phase of this study, when it will be fully operational and capable of guiding discussions about prioritizing the development and introduction of new vaccines.
Keywords: Health and Medicine

Ranking Vaccines: Applications of a Prioritization Software Tool: Phase III: Use Case Studies and Data Framework - Institute of Medicine; National Academy of Engineering (The National Academies Press, 2015)
SMART Vaccines - Strategic Multi-Attribute Ranking Tool for Vaccines - is a prioritization software tool developed by the Institute of Medicine that utilizes decision science and modeling to help inform choices among candidates for new vaccine development. A blueprint for this computer-based guide was presented in the 2012 report Ranking Vaccines: A Prioritization Framework: Phase I. The 2013 Phase II report refined a beta version of the model developed in the Phase I report. Ranking Vaccines: Applications of a Prioritization Software Tool: Phase III: Use Case Studies and Data Framework extends this project by demonstrating the practical applications of SMART Vaccines through use case scenarios in partnership with the Public Health Agency of Canada, New York State Department of Health, and the Serum Institute of India. This report also explores a novel application of SMART Vaccines in determining new vaccine product profiles, and offers practical strategies for data synthesis and estimation to encourage the broader use of the software.
Keywords: Health and Medicine

Vaccines for the 21st Century: A Tool for Decisionmaking - Institute of Medicine (The National Academies Press, 2000)
Vaccines have made it possible to eradicate the scourge of smallpox, promise the same for polio, and have profoundly reduced the threat posed by other diseases such as whooping cough, measles, and meningitis. What is next? There are many pathogens, autoimmune diseases, and cancers that may be promising targets for vaccine research and development. This volume provides an analytic framework and quantitative model for evaluating disease conditions that can be applied by those setting priorities for vaccine development over the coming decades. The committee describes an approach for comparing potential new vaccines based on their impact on morbidity and mortality and on the costs of both health care and vaccine development. The book examines:
Keywords: Health and Medicine

Ranking Vaccines: A Prioritization Software Tool: Phase II: Prototype of a Decision-Support System - Institute of Medicine (The National Academies Press, 2013)
SMART Vaccines—Strategic Multi-Attribute Ranking Tool for Vaccines—is a prioritization software tool developed by the Institute of Medicine that utilizes decision science and modeling to help inform choices among candidates for new vaccine development. A blueprint for this computer-based guide was presented in the 2012 report Ranking Vaccines: A Prioritization Framework: Phase I. Ranking Vaccines: A Prioritization Software Tool,Phase II extends the proof-of-concept presented in the Phase I report, which was based on multi-attribute utility theory. This report refines a beta version of the model developed in the Phase I report and presents its next iteration, SMART Vaccines 1.0. Ranking Vaccines: Phase II discusses the methods underlying the development, validation, and evaluation of SMART Vaccines 1.0. It also discusses how SMART Vaccines should—and, just as importantly, should not—be used. The report also offers ideas for future enhancements for SMART Vaccines as well as for ideas for expanded uses and considerations and possibilities for the future.
Keywords: Health and Medicine

The Childhood Immunization Schedule and Safety: Stakeholder Concerns, Scientific Evidence, and Future Studies - Institute of Medicine (The National Academies Press, 2013)
Vaccines are among the most safe and effective public health interventions to prevent serious disease and death. Because of the success of vaccines, most Americans today have no firsthand experience with such devastating illnesses as polio or diphtheria. Health care providers who vaccinate young children follow a schedule prepared by the U.S. Advisory Committee on Immunization Practices. Under the current schedule, children younger than six may receive as many as 24 immunizations by their second birthday. New vaccines undergo rigorous testing prior to receiving FDA approval; however, like all medicines and medical interventions, vaccines carry some risk. Driven largely by concerns about potential side effects, there has been a shift in some parents' attitudes toward the child immunization schedule. The Childhood Immunization Schedule and Safety identifies research approaches, methodologies, and study designs that could address questions about the safety of the current schedule. This report is the most comprehensive examination of the immunization schedule to date. The IOM authoring committee uncovered no evidence of major safety concerns associated with adherence to the childhood immunization schedule. Should signals arise that there may be need for investigation, however, the report offers a framework for conducting safety research using existing or new data collection systems.
Keywords: Health and Medicine

Immunization Safety Review: Thimerosal-Containing Vaccines and Neurodevelopmental Disorders - Institute of Medicine (The National Academies Press, 2001)
In this report, the Immunization Safety Review committee examines the hypothesis of whether or not the use of vaccines containing the preservative thimerosal can cause neurodevelopmental disorders (NDDs), specifically autism, attention deficit/hyperactivity disorder (ADHD), and speech or language delay.
Keywords: Health and Medicine

Eliminating the Public Health Problem of Hepatitis B and C in the United States: Phase One Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Hepatitis B and C cause most cases of hepatitis in the United States and the world. The two diseases account for about a million deaths a year and 78 percent of world's hepatocellular carcinoma and more than half of all fatal cirrhosis. In 2013 viral hepatitis, of which hepatitis B virus (HBV) and hepatitis C virus (HCV) are the most common types, surpassed HIV and AIDS to become the seventh leading cause of death worldwide.
Keywords: Health and Medicine

The Domestic and International Impacts of the 2009-H1N1 Influenza A Pandemic: Global Challenges, Global Solutions: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
In March and early April 2009, a new, swine-origin 2009-H1N1 influenza A virus emerged in Mexico and the United States. During the first few weeks of surveillance, the virus spread by human-to-human transmission worldwide to over 30 countries. On June 11, 2009, the World Health Organization (WHO) raised the worldwide pandemic alert level to Phase 6 in response to the ongoing global spread of the novel influenza A (H1N1) virus. By October 30, 2009, the H1N1 influenza A had spread to 191 countries and resulted in 5,700 fatalities. A national emergency was declared in the United States and the swine flu joined SARS and the avian flu as pandemics of the 21st century. Vaccination is currently available, but in limited supply, and with a 60 percent effectiveness rate against the virus.
Keywords: Health and Medicine

Adverse Effects of Vaccines: Evidence and Causality - Institute of Medicine (The National Academies Press, 2012)
In 1900, for every 1,000 babies born in the United States, 100 would die before their first birthday, often due to infectious diseases. Today, vaccines exist for many viral and bacterial diseases. The National Childhood Vaccine Injury Act, passed in 1986, was intended to bolster vaccine research and development through the federal coordination of vaccine initiatives and to provide relief to vaccine manufacturers facing financial burdens. The legislation also intended to address concerns about the safety of vaccines by instituting a compensation program, setting up a passive surveillance system for vaccine adverse events, and by providing information to consumers. A key component of the legislation required the U.S. Department of Health and Human Services to collaborate with the Institute of Medicine to assess concerns about the safety of vaccines and potential adverse events, especially in children.
Keywords: Health and Medicine

Immunization Safety Review: Measles-Mumps-Rubella Vaccine and Autism - Institute of Medicine (The National Academies Press, 2001)
Immunization is widely regarded as one of the most effective and beneficial tools for protecting the public's health. In the United States, immunization programs have resulted in the eradication of smallpox, the elimination of polio, and the control and near elimination of once-common, often debilitating and potentially life-threatening diseases, including measles, mumps, rubella, diphtheria, pertussis, tetanus, and Haemophilus influenza type b.
Keywords: Health and Medicine

Priorities for the National Vaccine Plan - Institute of Medicine (The National Academies Press, 2010)
Vaccination is a fundamental component of preventive medicine and public health. The use of vaccines to prevent infectious diseases has resulted in dramatic decreases in disease, disability, and death in the United States and around the world. The current political, economic, and social environment presents both opportunities for and challenges to strengthening the U.S. system for developing, manufacturing, regulating, distributing, funding, and administering safe and effective vaccines for all people. Priorities for the National Vaccine Plan examines the extraordinarily complex vaccine enterprise, from research and development of new vaccines to financing and reimbursement of immunization services. Priorities for the National Vaccine Plan examines the extraordinarily complex vaccine enterprise, from research and development of new vaccines to financing and reimbursement of immunization services. The book makes recommendations about priority actions in the update to the National Vaccine Plan that are intended to achieve the objectives of disease prevention and enhancement of vaccine safety. It is centered on the plan's five goals in the areas of vaccine development, safety, communication, supply and use, and global health.
Keywords: Health and Medicine

Ending Neglect: The Elimination of Tuberculosis in the United States - Institute of Medicine (The National Academies Press, 2000)
Tuberculosis emerged as an epidemic in the 1600s, began to decline as sanitation improved in the 19th century, and retreated further when effective therapy was developed in the 1950s. TB was virtually forgotten until a recent resurgence in the U.S. and around the world—ominously, in forms resistant to commonly used medicines. What must the nation do to eliminate TB? The distinguished committee from the Institute of Medicine offers recommendations in the key areas of epidemiology and prevention, diagnosis and treatment, funding and organization of public initiatives, and the U.S. role worldwide. The panel also focuses on how to mobilize policy makers and the public to effective action. The book provides important background on the pathology of tuberculosis, its history and status in the U.S., and the public and private response. The committee explains how the U.S. can act with both self-interest and humanitarianism in addressing the worldwide incidence of TB.
Keywords: Health and Medicine

Immunization Safety Review: Vaccinations and Sudden Unexpected Death in Infancy - Institute of Medicine (The National Academies Press, 2003)
With current recommendations calling for infants to receive multiple doses of vaccines during their first year of life and with sudden infant death syndrome (SIDS) the most frequent cause of death during the postneonatal period, it is important to respond to concerns that vaccination might play a role in sudden unexpected infant death.
Keywords: Health and Medicine

Vaccine Safety Research, Data Access, and Public Trust - Institute of Medicine (The National Academies Press, 2005)
The Vaccine Safety Datalink (VSD) is a large, linked database of patient information that was developed jointly by CDC and several private managed care organizations in 1991. It includes data on vaccination histories, health outcomes, and characteristics of more than 7 million patients of eight participating health organizations. Researchers from CDC and the managed care groups have used VSD information to study whether health problems are associated with vaccinations. The subsequent VSD data sharing program was launched in 2002 to allow independent, external researchers access to information in the database.
Keywords: Health and Medicine

Financing Vaccines in the 21st Century: Assuring Access and Availability - Institute of Medicine (The National Academies Press, 2004)
The national immunization system has achieved high levels of immunization, particularly for children. However, this system faces difficult challenges for the future. Significant disparities remain in assuring access to recommended vaccines across geographic and demographic populations. These disparities result, in part, from fragmented public–private financing in which a large number of children and adults face limited access to immunization services. Access for adults lags well behind that of children, and rates of immunizations for those who are especially vulnerable because of chronic health conditions such as diabetes or heart and lung disease, remain low.
Keywords: Health and Medicine

Battling Malaria: Strengthening the U.S. Military Malaria Vaccine Program - Institute of Medicine (The National Academies Press, 2006)
Malaria is an infectious disease common to several parts of the world, including Africa, northern South America, and Asia. During their service in the military, U.S. active members may be sent to any part of the world, including parts of the world where Malaria is an issue. In Liberia in 2003, for example, there was a 28 percent attack rate in Marines who spent a short time ashore, and half of the 80 Marines affected needed to be evacuated to Germany. This was not only costly to the U.S. military but dangerous as well. To fight against this disease, there exists a Malaria Vaccine program in the U.S. military. However, there exists a variety of potential vaccine targets for the most severe and important form of malaria; malaria from the species Plasmodium falciparum. Issues also arise with the fact that there are three possible stages to create vaccines against—preerythrocytic, blood, or transmission.
Keywords: Conflict and Security Issues; Health and Medicine

Adverse Events Associated with Childhood Vaccines: Evidence Bearing on Causality - Institute of Medicine (The National Academies Press, 1994)
Childhood immunization is one of the major public health measures of the 20th century and is now receiving special attention from the Clinton administration. At the same time, some parents and health professionals are questioning the safety of vaccines because of the occurrence of rare adverse events after immunization. This volume provides the most thorough literature review available about links between common childhood vaccines—tetanus, diphtheria, measles, mumps, polio, Haemophilus influenzae b, and hepatitis B—and specific types of disorders or death. The authors discuss approaches to evidence and causality and examine the consequences—neurologic and immunologic disorders and death—linked with immunization. Discussion also includes background information on the development of the vaccines and details about the case reports, clinical trials, and other evidence associating each vaccine with specific disorders. This comprehensive volume will be an important resource to anyone concerned about the immunization controversy: public health officials, pediatricians, attorneys, researchers, and parents.
Keywords: Health and Medicine

Adverse Effects of Pertussis and Rubella Vaccines - Institute of Medicine (The National Academies Press, 1991)
Parents have come to depend on vaccines to protect their children from a variety of diseases. Some evidence suggests, however, that vaccination against pertussis (whooping cough) and rubella (German measles) is, in a small number of cases, associated with increased risk of serious illness. This book examines the controversy over the evidence and offers a comprehensively documented assessment of the risk of illness following immunization with vaccines against pertussis and rubella. Based on extensive review of the evidence from epidemiologic studies, case histories, studies in animals, and other sources of information, the book examines:
Keywords: Health and Medicine

DPT Vaccine and Chronic Nervous System Dysfunction: A New Analysis - Institute of Medicine (The National Academies Press, 1994)
Keywords: Health and Medicine